Fundamentals of Computational Geoscience Numerical Methods and Algorithms - Zhao, Chongbin; Hobbs, Bruce E.; Ord, Alison (Lecture Notes in Earth Sciences,, 2009)
This monograph aims to provide state-of-the-art numerical methods, procedures and algorithms in the field of computational geoscience, based on the authors' own work during the last decade. Although some theoretical results are provided to verify numerical ones, the main focus of this monograph is on computational simulation aspects of the newly-developed computational geoscience discipline. The advanced numerical methods, procedures and algorithms presented are also applicable to a wide range of problems in both geological length-scales and engineering length-scales. In order to broaden the readership, common mathematical notations are used to describe the theoretical aspects of geoscience problems, making it either an invaluable textbook for postgraduate students or an indispensable reference book for computational geoscientists, mathematicians, engineers and geoscientists.